Synthetic diversity in the preparation of metallic uranium. Issue 3 (23rd March 2022) - Jang, Harry; Louis-Jean, James; Childs, Bradley; Holliday, Kiel; Reilly, Dallas; Athon, Matthew; Czerwinski, Kenneth; Hatchett, David; Poineau, Frederic
Abstract : Uranium metal is associated with several aspects of nuclear technology; it is used as fuel for research and power reactors, targets for medical isotope productions, explosive for nuclear weapons and precursors in synthetic chemistry. The study of uranium metal at the laboratory scale presents the opportunity to evaluate metallic nuclear fuels, develop new methods for metallic spent fuel reprocessing and advance the science relevant to nuclear forensics and medical isotope production. Since its first isolation in 1841, from the reaction of uranium chloride and potassium metal, uranium metal has been prepared by solid-state reactions and in solution by electrochemical, chemical and radiochemical methods. The present review summarizes the methods outlined above and describes the chemistry associated with each preparation.